The Association between Type 2 Diabetes Mellitus and The Outcome of COVID-19 Patients at Sanglah Hospital in 2020-2022 - Upadhana, Putu Sayakumara; Sastrawan, I Gede Gita; Rahmautami, I Gita Dewi; Merry, Merry; Daradila, Ni Putu Kostarika Melia; Sutanto, Derian Adiguna; Pertiwi Manuaba, Ida Ayu Santhi; Hartadi, Putu Ardy; Ratna Kinasih, Komang Vika Nariswari; Sudarmika, Putu (Jurnal Penyakit Dalam Indonesia, 2022)
Introduction.People with type 2 diabetes mellitus (T2DM) are at a higher risk of mortality from COVID-19. This study aimed to identify the relationship between T2DM and the outcome of COVID-19 patients in Sanglah Hospital Denpasar, Bali. Methods. An observational analytic study with a cross-sectional approach was conducted among COVID-19 patients. We used secondary data from the records of confirmed COVID-19 patients who were treated at Sanglah Hospital on 1 August 2020 – 28 February 2022. Sample were selected with total sampling technique. Results. There were 1,056 patients involved in this study. Most of the patients were male (n=571; 54.1%), with a median age of 59 years old. Most of the patients were categorized as severe COVID-19 (n=641; 60.7%). A total of 275 patients had T2DM (26.0%). Chi-square analysis showed a significant association of T2DM with mortality (PR=1.422; 95%CI=1.162-1.742; p=0.001), severe COVID-19 (PR=1.726; 95%CI=1.365-2.184; p<0.001), ventilator usage (PR=1.334; 95%CI=1.093-1.791; p=0.045), and longer hospitalization duration (PR=1.340; 95%CI=1.083-1.658; p=0.006) with T2DM. Logistic regression analysis showed significant association of T2DM with mortality (PR=1.536; 95%CI=1.110-2.125; p=0.010), severe COVID-19 (PR=1.704; 95%CI=1.233-2.356; p<0.001), and longer hospitalization duration (PR=1.615; 95%CI=1.191-2.190; p=0.002).